Multi-objective optimization of cross laminated timber-concrete composite floor using NSGA-II. (15th July 2022) - Van Thai, Minh; Galimard, Philippe; Elachachi, Sidi Mohammed; Ménard, Sylvain
Abstract: Cross-laminated timber (CLT) is an engineered wood product made of multiple glued layers in the form of a panel suitable for flooring systems. CLT can also be mechanically connected to the concrete layer using the connector systems to create a CLT-concrete composite (CCC). This concept enhanced the structural performance of the floor and could be adopted for mid-and high-rise buildings. However, the design of the CCC floor involves the optimization of multiple structural and non-structural elements. In this study, we tackle the gap in the literature by carrying out a multi-objective optimization of the CCC floor with notched connectors by minimizing total thickness, total weight, and total material cost considering structural, vibration comfort, and especially, fire conditions constraints using the well-developed genetic algorithm (NSGA-II). The optimal solutions are presented in the Pareto fronts of multiple floor spans and cost ratio timber/concrete. The study also gives insight into the influence of design parameters and the governing design constraint. However, we only focus on one type of floor (CCC) and do not implement the environmental aspect of the structure. Highlights: Optimization multi-objective of CLT-concrete composite floor structures to minimize weight, thickness, and cost. Floor designs comply to Canadian standard of timber construction CSA-O86:2019. Comparison between the common design and the optimal ones of the Pareto front. Parametric study on the influence of floor span and the cost ratio timber/concrete.